ChemInform Abstract: Spin and Dipole Ordering in Ni2InSbO6 and Ni2ScSbO6 with Corundum‐Related Structure. Issue 25 (3rd June 2013) - Mathieu, R.; et al., et al.
Abstract The title compounds are prepared by solid state reaction of NiO, Sc2O3 or In2O3, and Sb2O5 (1300 °C, 24 h).